2015
DOI: 10.1016/j.juro.2014.11.088
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after Radical Cystectomy: Impact of Obesity Versus Adiposity after Adjusting for Skeletal Muscle Wasting

Abstract: Purpose We assess the impact of obesity, as measured conventionally by body mass index vs excess adiposity as measured by fat mass index, on mortality after radical cystectomy for bladder cancer, adjusting for the presence of skeletal muscle wasting. Materials and Methods This retrospective cohort study included 262 patients treated with radical cystectomy for bladder cancer between 2000 and 2008 at the Mayo Clinic. Lumbar skeletal muscle and adipose compartment areas were measured on preoperative imaging. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 29 publications
0
53
0
Order By: Relevance
“…This can surely cause differences in the indication for RC, extent of lymphadenectomy, histopathological assessment or quality of TUR-BT. Moreover, by investigating BMI we cannot distinguish between fat and muscle, as BMI is not an anthropometric measure that can assume body composition [31]. In addition to body composition, sarcopenia as a surrogateparameter of frailty was not assessed and therefore, the model was not adjusted for it [32].…”
Section: Discussionmentioning
confidence: 99%
“…This can surely cause differences in the indication for RC, extent of lymphadenectomy, histopathological assessment or quality of TUR-BT. Moreover, by investigating BMI we cannot distinguish between fat and muscle, as BMI is not an anthropometric measure that can assume body composition [31]. In addition to body composition, sarcopenia as a surrogateparameter of frailty was not assessed and therefore, the model was not adjusted for it [32].…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% accrued nutritional data retrospectively, similar to the 87% reported in 2007 52 . Psutka et al 41 conducted sensibility analysis to test for possible bias introduced by the exclusion of patients with missing data, but this was unfortunately not discussed in the majority of the literature reported here. Many studies also observed the impact of BMI on complications and mortality after RC using regression models.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies investigated the association between BMI and RC outcomes [33][34][35][36][37][38][39][40][41][42][43][44] . Reyes et al 33 found that tract infections, pyelonephritis, wound infections and overall complications were less frequent in normal-weight patients (18.5-24.9kg/m 2 ) compared to overweight (25-29.9kg/m 2 ) and obese (≄30.0kg/m 2 ) patients.…”
Section: Body Mass Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies described sarcopenia as a novel prognostic factor for predicting survival in patients with various cancers, including colorectal cancer, pancreatic cancer, hepatocellular carcinoma, renal cell carcinoma, UC, and gastroesophageal cancer. [2][3][4][5][6][7] Only two studies have investigated the relationship between the sarcopenia status and clinical outcomes of UTUC patients treated with RNU.…”
Section: Introductionmentioning
confidence: 99%